Sejarah Hukum Kekosongan Presiden dan Wakil Presiden Bersamaan di Indonesia (Pelajaran dari Rezim Otoriter Sukarno dan Soeharto) - Ramadhan, Febriansyah (Universitas Islam Indonesia, 2026)
Indonesia has a history of simultaneous vacuums of power on the presidential and vice-presidential seats that have received little academic attention. This article examines the said history, namely the Emergency Government of the Republic of Indonesia (PDRI) of 1948–1949 and the transition of power from President Soekarno to Soeharto in 1966–1968. This article conducts a longitudinal study of both instances and the legal instruments surrounding them, uncovering various historical lessons that can inspire the development of future presidential succession law and examining the current presidential succession law in Article 8 paragraph (3) of the 1945 Constitution of the Republic of Indonesia from a legal historical perspective. This article is a normative legal research with a legal historical approach. To enrich the study, this article uses sources from classical archives surrounding both events and the Minutes of the MPR Sessions of 1966–1968 and 1973, for critical study. This article argues that the history of vacuums of power in Indonesia demonstrates a gradual transition from the practice of power vacuums based on political decisions toward the institutionalization of presidential succession law, although this has not yet fully translated into constitutional supremacy. Using a legal history approach to the phases from the PDRI (Indonesian Democratic Republic of Indonesia), the New Order transition, to constitutional reform, this article aims to demonstrate that Indonesia experienced a gradual evolution in the development of presidential succession law, moving from a shift away from political control toward constitutional supremacy, which fully requires an automatic succession process. However, many historical lessons do not inspire the presidential succession law in Article 8 paragraph (3) of the 1945 Constitution of the Republic of Indonesia, and in some cases, it has even experienced normative regression.